In what way does music improve learning in medical education? a systematic review - Minhat, Halimatus Sakdiah; Zakariah, Siti Zulaikha; Ibrahim, Rosni; Mohamed Razali, Camelia Siti Maya (Faculty of Medicine and Health Sciences, UPM, 2022)
Introduction: Music has been widely used in teaching and learning due to its observed positive effects. This review aimed to identify the beneficial impacts of music utilization in medical education. Methods: Using four established databases; Scopus, ScienceDirect, JSTOR and PubMed, exhaustive searched of related articles were performed for articles published between January 2010 and January 2020 using combination of keywords. Screening of titles and abstracts were conducted, with removal of duplicates. Results: Five full text articles were finally reviewed, of which one cross-sectional, three intervention and a qualitative studies. Consensus between authors had successfully identified three themes, which were positive effect of music on the well-being and performance of the medical students, as well as improved patient-doctor communication skills. Conclusion: The findings of the review confirmed the positive effects of music utilization on the well-being and performance of medical students, as well as on patient-doctor communication skills.